Evaluación del efecto de la aplicación del ozono (o3) para el control del hongo ascochyta en Arveja (pisum sativum) en el sector de Salache, provincia Cotopaxi, periodo 2021. - Chicaiza Chuquitarco, Oscar Emilio (2021)
The research was carried out at the Technical University of Cotopaxi Salache sector in Andean projects in controlled climate, the effect of the application of ozone (O3) was evaluated for the control of the ascochyta fungus in pea (Pisum Sativum) in the Salache sector, province of Cotopaxi period 2021 this work. A Completely Randomized (AXB) design was used, with 6 treatments and 3 repetitions, with Tukey tests at 5%; The results of the research through the application of ozonated water with the respective concentrations 1pp + 6 applications, 2ppm + 4 applications on days 1, 10, and 20 on day 1 there are significant differences for concentrations for the rest of the variables did not exist significant difference. A coefficient of variation of 12.8% was obtained. When performing the Tukey 5% test, it shows the means of each of the concentrations to decrease the severity after the use of ozonated water, 2 ranges of statistical significance were found, in the first range A, the concentration c2 (2ppm) and c1 (1pmm) were located with averages of 31.61 and 32.69% severity, at the end there is the control with 42.35% in range B, on day 10 there are significant difference for concentrations A coefficient of variation of 16.15% was obtained, On day 20 there are significant differences for concentrations. A coefficient of variation of 17.2% was obtained, In the height of the stem on day 20 A coefficient of variation of 3.74% was obtained, and the diameter of the stem on day 20 was obtained there was no statistical significance. A coefficient of variation of 2.07% was obtained.